Comprehensive Review of Foundational Advances Across Healthcare Disciplines - Algobisi, Norah Mohammad Brahem; AL Mutairi, Laila Faris; Al Otaibi, Shaher Mushabab Hajad; AlRasheed, Noura Mohammed; Al-Saadoun, Anoud Musab; Alotaibi, Bader Hmood; alhazmi, Aisha yahea; Alanezi, Aisha Hindi; alharbi, Mohammed aziz; Alshammary, Manal Ayyad (Journal of Ecohumanism, 2024)
Healthcare has also witnessed drastic changes in many fields of study, including medicine, nursing, pharmacy, dental and medicine, public health, and healthcare management. They have had a drastic positive impact in the short term on patient care, clinical practice/ bureaucracy, and the health of a nation, which has enhanced the health care systems in the world. This review looks at these basic innovations so that one can understand the kind of changes they underwent. Almost all advancements in treatments and technologies, changes in patient care models, and success at combating chronic and acute disease states have directly hinged on interdisciplinary strategies. The place such innovations take in the ongoing advancements in healthcare helps define the course that healthcare environments and patients are set to take in the future.